Aproximación epistemológica al sistema expositivo mediante la técnica de mapeo VOS, aplicación a los catálogos de exposiciones de la BNE publicados en Málaga y Valencia. - Pino-Díaz, José (My University, 2019)
The BNE uses "Exhibitions" of subject heading thesaurus to identify catalogs of an exhibition art under artistic subjects or names of artists, e.g. "Gothic Painting - Exhibitions". Also, since 2016, it uses "Exhibitions catalogs" of genre/form thesaurus. Authors, artists, curators, entities, institutions, cities, and terms of thesaurus, associated with each other through co-authorship and co-occurrence relationships, constitute a system, that is, a set of interrelated elements that orderly contribute to constitute and characterize the exhibition catalogs knowledge system, in the sense that the Actor-Network Theory describes. The Exhibitions catalogs of the BNE records, published in the cities of Málaga and Valencia in the period 2017-2019, constitute a system of knowledge. This system is visualized according to the similarity analysis method, taking the systemic association relations, as they appear in the XML file exported from the BNE. Both exhibition systems are mainly public, with little participation by foundations or private entities. The dominant central position of local institutions stands out in the Malaga system, mainly the Málaga City Council, followed by the Málaga Provincial Council. On the periphery of the network are the Picasso Museum Foundation Málaga and the company Gestión Cultural y Comunicación, which manages the Contemporary Art Centre (CAC) and the Museum of Art of the Provincial Council (MAD). The regional government, the Generalitat Valenciana, the local institutions, the University of Valencia and the Valencia City Council, and the Valencia Provincial Council, stand out in the Valencian system. The central position of the network is occupied by the Consortium of Museums of the Valencian Community, a public organisation constituted by the regional government, the provincial councils and the town councils of the three provincial capitals.
Epistemological approach to the exhibition system through the VOS mapping technique, application to the BNE exhibition catalogs published in Málaga and Valencia.
Comunicación presentada en el Foro Internacional sobre Catálogos, celebrado en el Centro Pompidou Málaga del 18 al 20 de septiembre de 2019.
Keywords: Biblioteca Nacional de España - Catálogos; Encabezamientos de materia españoles; Exposiciones - Encabezamientos de materia; Biblioteca Nacional de España; Thesaurus; Exhibition catalogs indexing; Málaga; Valencia; Exhibition knowledge system; Actor-Network Theory; Knowledge mapping; Visualization of similarity; Clustering